Application of the cost benefit analysis in the evaluation and selection of public projects (financial aspect) - Petrović, Dragana N.; Đedović, Branko N.; Petrović, Nikola Č. (Vojnotehnički glasnik / Military Technical Courier, 2013)
Cost-benefit analysis is very useful tool for evaluation and selection of public projects, especially those with expectancy 30 and more years, such as: building hospitals, irrigation canals, bridges, tunnels, development and production of new funds and new weapon and military equipment (WME) etc. The analysis is applied in the private sector, for the evaluation of projects whish are in one part financed by state funds or trought loans. The enterpeneur or the company which does not show interesting or do not have sufficient funds for realization projects (for the opening schools, theaters, etc). Cost-benefit analysis provides informations for government agencies and commercial banks about the profitability of investments, without which they can not make a decision of financial support for the projects realization. Selection of the best investment alternatives is realized on the basis of financial and economic analysis, as two integral parts of the cost-benefit analysis. The content of this paper are the financial analysis that examines the financial viability of the project only from the standpoint of the sponsor and financier. In one of the next issues of the journal, we will process and economic analysis as well as a complete analysis of the effectiveness of the project.